Aggression in Legal Limbo: A Gap in the Law that Needs Closing - Donald M. Ferencz (Washington University Global Studies Law Review, 2013)
The International Criminal Court’s present inability to exercise its jurisdiction over the crime of aggression leaves a glaring gap in the enforcement of international law. After briefly addressing the current status of the crime of aggression, I will relate some of my own reaction to my father’s conviction that something must be done—and done now—to hold accountable those who would undertake the illegal use of armed force, subjecting them, if possible, to prosecution for crimes against humanity.
Keywords: International Criminal Court; ICC; crimes against humanity; jurisdiction; aggression